Mechanism(s) of Membrane Permeability Transition in Liver Mitochondria of Lamprey, Lampetra fluviatilis L. during Pre-spawning Starvation - Belyaeva, Elena A. (Recent Developments in Medicine and Medical Research Vol. 16, 2021)
As we have found before, an opening of mitochondrial permeability transition (MPT) pore in its low conductance state takes place in hepatocytes of the Baltic lamprey (Lampetra fluviatilis L.) during reversible metabolic depression in the period of its pre-spawning migration when the exogenous feeding is switched off. The depression is observed in the last year of the lamprey life cycle and is mediated by reversible mitochondrial dysfunction (mitochondrial uncoupling in winter and the coupling in spring). The objective of the present study was to further underscore the mechanism(s) of the MPT pore induction in the lamprey liver, for which we used Ca2+ plus Pi (and/or laurate) and Cd2+ as the pore inducers. It was shown that Ca2+ plus Pi induced the high-amplitude swelling of the isolated “winter” mitochondria both in isotonic sucrose and ammonium nitrate medium, while both low and high Cd2+ did not produce the mitochondrial swelling in these assay media. Low Cd2+ enhanced the inhibition of basal respiration rate of the “winter” mitochondria energized by NAD-dependent substrates, whereas the same concentrations of the heavy metal evoked its partial stimulation on FAD-dependent substrates. The above mentioned changes produced by Cd2+ or Ca2+ plus Pi in the “winter” mitochondria were only weakly sensitive to cyclosporine A, CsA (a potent pharmacological desensitizer of the MPT pore) added alone and they were not sensitive to dithiothreitol (a dithiol reducing agent, DTT). Measuring trans-membrane potential of the “spring” lamprey liver mitochondria, we obtained that Cd2+ produced its decline on both types of the respiratory substrates under test that was significantly slowed down by CsA; besides, the membrane potential was partially restored by DTT. The revealed seasonal changes in action of different membrane permeability and electron transport chain (mitoETC) modulators, such as heparin, nupercaine, laurate, BSA, CsA, DTT, and heavy metals on the lamprey liver mitochondria function are discussed, as well as the reversible season-dependent disturbance of complex I (CI) activity of mitoETC (including its reverse electron transport), which points to the possible involvement of A/D conversion of CI in the MPT pore formation and/or regulation during the reversible metabolic depression of the animal, strengthening the physiological relevance of the phenomenon.